Lie beside me : a novel - Lodge, Gytha (Random House, 2021)
"Louise wakes up. Her head aches, her mouth is dry, her memory is fuzzy. But she suspects she's done something bad. She rolls over towards her husband, Niall. The man who, until recently, made her feel loved. But it's not Niall who's lying beside her. In fact, she's never seen this man before. And he's not breathing . . . As Louise desperately struggles to piece her memories back together, it's clear to Detective Jonah Sheens and his team that she is their prime suspect--though they soon find she's not the only one with something to hide. Did she do it? And, if not, can they catch the real killer before they strike again?"--